Psychological Outcome in Young Survivors of Severe TBI: A Cross-Informant Comparison - Karoline Doser; Ingrid Poulsen; Anne Norup (Behavioural Neurology)
Objective. To investigate the psychological outcome and the agreement between self-ratings and proxy-ratings in young individuals after severe traumatic brain injury (TBI). Methods. Twenty pairs of former patients who sustained a severe TBI in their adolescence or early adulthood and their significant others (SOs) were contacted around 66 months after injury to complete a measure of psychological and behavioral problems. The Adult Self-Report 18–59 and the Adult Behavior Checklist 18–59 were used. Results. Results showed significant differences compared to the normative sample in the domains withdrawal, attention, and intrusive and internalizing problems. Good or excellent levels of agreement were found between the self-rating and the proxy-rating in overt areas such as somatic complaints and aggressive and intrusive behavior. Fair or poor levels of agreement were found in nonovert areas such as anxiety and depression, withdrawal, thought and attention problems, and personal strength. Conclusion. The findings show that young patients experience psychological dysfunction. Our study suggests that the use of either a self-rating or a proxy-rating would be appropriate for evaluating overt domains, regarding the good to excellent levels of agreement. However, in nonovert domains, such as withdrawal and attention, an additional proxy-rating from a SO could provide supplementary information and build a more complete objective assessment.